Vegetable Preferences among Preschoolers in Kuantan, Pahang - Shaharudin, Nursyafiqah; Sari, Pramitha; Jaafar, Nurul Hazirah (International Journal of Allied Health Sciences, 2025)
Background: Vegetable intake among Malaysian children remains insufficient, despite its role in supporting healthy growth. While previous studies have explored overall vegetable intake and contributing factors, limited research has specifically focused on children’s vegetable preferences and their association with parental feeding practices. Therefore, this study aimed to identify the vegetables preferred by preschoolers, assess common parental feeding practices, and examine the relationship between these practices and children’s preferences. Methods: A total of 44 caregiver-child pairs were recruited through convenience sampling. Children aged 4 to 6 years and their primary caregivers were included, with those having medical conditions affecting diet excluded. Data were collected using validated questionnaires, including the Comprehensive Feeding Practices Questionnaire (CFPQ) and visual-based vegetable preference assessment. Data were analysed using descriptive statistics to summarise vegetable preferences and parental feeding practices, and Pearson’s correlation to assess the relationship between them. Results: A total of 44 caregiver-child pairs participated in the study. Carrot, broccoli, and tomato were the most preferred vegetables, while mustard leaf, capsicum, and lady’s finger were the least liked. The most common feeding practices reported were “restriction for weight control,” “modelling,” and “monitoring.” A significant negative correlation was observed between the “child control” subscale and vegetable preferences (r = -0.300, n = 44, p = 0.048), while a significant positive correlation was found with “encourage balance and variety” (r = 0.314, n = 44, p = 0.038). Conclusion: Specific parental feeding practices, especially those that are supportive and involve structured feeding strategies, particularly those promoting balance and variety, are essential for fostering vegetable acceptance and healthier dietary habits from an early age.